Bacteria co-culture adhesion on different texturized zirconia surfaces. (November 2021) - Dantas, Telma; Padrão, Jorge; da Silva, Mariana Rodrigues; Pinto, Paulo; Madeira, Sara; Vaz, Paula; Zille, Andrea; Silva, Filipe
Abstract: Zirconia is becoming reckoned as a promising solution for different applications, in particular those within the dental implant investigation field. It has been proved to successfully overcome important limitations of the commonly used titanium implants. The adhesion of microorganisms to the implants, in particular of bacteria, may govern the success or the failure of a dental implant, as the accumulation of bacteria on the peri-implant bone may rapidly evolve into periodontitis. However, bacterial adhesion on different zirconia architectures is still considerably unknown. Therefore, the adhesion of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa to zirconia surfaces with different finishings was evaluated and compared to a titanium surface. The adhesion interaction between S. aureus and P. aeruginosa was also evaluated using a co-culture since these bacteria are infamous due to their common presence in chronic wound infections. Results showed that different bacterium species possess different properties which influence their propensity to adhere to different roughness levels and architectures. E. coli revealed a higher propensity to adhere to zirconia channelled surfaces (7.15 × 10 6  CFU/mL), whereas S. aureus and P. aeruginosa adhered more to the titanium control group (1.07 × 10 5  CFU/mL and 8.43 × 10 6  CFU/mL, respectively). Moreover, the co-culture denoted significant differences on the adhesion behaviour of bacteria. Despite not having shown an especially better behaviour regarding bacterial adhesion, zirconia surfaces with micro-channels are expected to improve the vascularization around the implants and ultimately enhance osseointegration, thus being a promising solution for dental implants. Graphical abstract: Image 1 Highlights: Zirconia is becoming reckoned as a promising solution for different applications. The adhesion of E. coli, S. aureus and P. aeruginosa to zirconia surfaces with different finishings was evaluated. E. coli revealed a higher propensity to adhere to zirconia channelled surfaces. S. aureus and P. aeruginosa adhered more to the titanium control group. Channelled zirconia surfaces are expected to improve the vascularization around the implants and enhance osseointegration.